1990
DOI: 10.1152/ajpregu.1990.259.5.r943
|View full text |Cite
|
Sign up to set email alerts
|

Neurons controlling cardiovascular responses to emotion are located in lateral hypothalamus-perifornical region

Abstract: We did four experiments to determine whether the lateral hypothalamus-perifornical (LH/PF) region is the source of neuronal cell bodies responsible for producing the cardiovascular (CV) responses associated with emotion or the defense reaction. Of particular concern was whether the paraventricular nucleus (PVN) plays a role in the generation of these CV responses. Mapping the hypothalamus with electrical stimulation showed that the CV pattern of responses was never produced by stimulating the PVN and was invar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
29
0

Year Published

1991
1991
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 0 publications
3
29
0
Order By: Relevance
“…This second mechanism of FSS can explain the observation that the kind of FSS that is assessed by actual consumption rather than by CS preference remains intact even after ORB l and AMYG lesions (Hatfield et al, 1996;Dunn and Everitt, 1988 (Braesicke, et al 2005). This influence is relayed from the hypothalamus to cardiovascular regulatory neurons in the medulla (Smith et al, 1990;Nakamura et al, 1992;Zhang et al, 2005Zhang et al, , 2006. The component of the blood pressure variable attributable to appetitive or aversive stimuli, B, is calculated as follows: …”
Section: Supplementary Equation Appendixmentioning
confidence: 99%
“…This second mechanism of FSS can explain the observation that the kind of FSS that is assessed by actual consumption rather than by CS preference remains intact even after ORB l and AMYG lesions (Hatfield et al, 1996;Dunn and Everitt, 1988 (Braesicke, et al 2005). This influence is relayed from the hypothalamus to cardiovascular regulatory neurons in the medulla (Smith et al, 1990;Nakamura et al, 1992;Zhang et al, 2005Zhang et al, , 2006. The component of the blood pressure variable attributable to appetitive or aversive stimuli, B, is calculated as follows: …”
Section: Supplementary Equation Appendixmentioning
confidence: 99%
“…The often controversial results regarding the magnitude and direction of effects are due to a site specificity and difference in methodology [17]. The LH/PFx region seems to be involved in the cardiovascular responses ac companying emotional behavior [39]. Destruction of the LH/PFx region has been shown to abolish cardiovascular but not behavioral responses associated with emotion [26,39], thus pointing to a dissociation of the various levels of the stress response each of which may involve different mechanisms of action in terms of signalling pathways (cir cuitry) and compounds (neurotransmitters and -pep tides).…”
mentioning
confidence: 99%
“…These regions project to a specific region of the hypothalamus (defined as comprising the perifornical region and the medial portion of the lateral hypothalamus) which was consequently termed HACER (Hypothalamic Area Controlling Emotional Responses). Efferents of the HACER have in turn been identified (32) and share the common property of sending relatively direct inputs to the intermediolateral column cells of the thoracic cord (major group of autonomic cells) (33). Other studies further suggested that the hypothalamic paraventricular nucleus contained separate but interacting populations of cells mediating differentially autonomic and endocrine responses, making of this nucleus a locus of endocrine and autonomic integration (34).…”
Section: Neuronal Systemsmentioning
confidence: 99%